Data from: Genetic differentiation within multiple common grassland plants supports seed transfer zones for ecological restoration - Durka, Walter; Michalski, Stefan G.; Berendzen, Kenneth W.; Bossdorf, Oliver; Bucharova, Anna; Hermann, Julia-Maria; Hölzel, Norbert; Kollmann, Johannes (Dryad, 2016)
Ecological restoration of grasslands is increasingly based on regional
seeds derived from predefined seed transfer zones. However, the degree and
spatial pattern of genetic differentiation among provenances of different
seed transfer zones is largely unknown. We assessed the genetic
differentiation among eight out of 22 German seed transfer zones for seven
common grassland species (Arrhenatherum elatius, Centaurea jacea, Daucus
carota, Galium album, Hypochaeris radicata, Knautia arvensis and Lychnis
flos-cuculi) using AFLP markers. We analysed genetic population structure
with AMOVA and Bayesian cluster analysis and tested for isolation by
distance and isolation by environment. In all of the investigated species,
almost all pairs of provenances were genetically differentiated. Bayesian
cluster analysis revealed species-specific numbers and spatial patterns of
gene pools, with between two (Arrhenatherum) and eight clusters (Lychnis).
Most investigated seed transfer zones represented a unique gene pool in
the majority of the species. We found isolation by distance in four
species, isolation by environment, driven by climatic seasonality, in
three species, and a lack of both in three species. Thus, the observed
genetic differentiation appears to be caused by both neutral and adaptive
processes. Synthesis and applications. Our study shows that grassland
plants are indeed strongly genetically differentiated across Germany
supporting the strategy of seed transfer zones for ecological restoration.
Although the predefined seed transfer zones are unlikely to match the
exact genetic structure of many species, they serve their purpose by
capturing a substantial amount of intraspecific genetic variation across
species.
Durka_et_al_2016_JAPPL_AFLPThis folder contains 7 files with AFLP data of
Durka et al. (2016) Genetic differentiation among multiple common
grassland plants supports seed transfer zones for ecological restoration.
Journal of Applied Ecology Arrhenatherum_elatius_AFLP.txt
Centaurea_jacea_AFLP.txt Daucus_carota_AFLP.txt Galium_album_AFLP.txt
Hypochaeris_radicata_AFLP.txt Knautia_arvensis_AFLP.txt
Lychnis_flos-cuculi_AFLP.txt Each files contains columns ID Individual
plant ID Pop Population identifier, i.e. one of 8 accessions n columns of
AFLP data with the first line giving the primer combination + fragment
length (e.g. ACA_CTGA_195) E Geographic coordinate of population in
decimal degrees: East N Geographic coordinate of population in decimal
degrees: North
Keywords: Hypochaeris radicata; Daucus carota; Centaurea jacea; isolation–by–distance; Holocene; Lychnis flos-cuculi; Knautia arvensis; Galium album; Ecological restoration; AFLP; Arrhenatherum elatius; local provenancing; seed transfer zone; isolation–by–environment